Pengaruh Brand Image, E-Service Quality, Dan Price terhadap Online Food Delivery - Pradana, Azizul Arundina; Kurniawati, Desi Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The objective of this research is to identify the effects of brand image, e-service quality, and price on the repurchase intention of ShopeeFood users. This study is categorized as an explanatory research as it explains the causal relationship between variables through hypothesis testing. Using non-probability sampling method and purposive sampling technique, 117 people, who are mostly students, were selected as the respondents. They are productive-age users of ShopeeFood in Malang city who have used the food delivery service at least twice and live in Malang city. The data was analyzed using multiple linear regression performed in SPSS version 25. This study finds that brand image significantly influences repurchase intention, that e-service quality significantly affects repurchase intention, and that price has a significant effect on repurchase intention. The findings indicate that an increase in brand image, e-service quality, and price will be followed by an increase in ShopeeFood users in Malang city. Abstrak The objective of this research is to identify the effects of brand image, e-service quality, and Price on the Repurchase Intention of ShopeeFood users. This study is categorized as explanatory research as it explains the causal relationship between variables through hypothesis testing. Using non-probability sampling method and purposive sampling technique, 117 people, who are mostly students, were selected as the respondents. They are productive-age users of ShopeeFood in Malang city who have used the food delivery service at least twice and live in Malang city. The data was analyzed using multiple linear regression performed in SPSS version 25. This study finds that Brand Image significantly influences repurchase intention, that E-Service Quality significantly affects repurchase intention, and that Price has a significant effect on repurchase intention. The findings indicate that an increase in brand image, e-service quality, and Price will be followed by an increase in ShopeeFood users in Malang city.